2017
DOI: 10.1163/22134808-00002554
|View full text |Cite
|
Sign up to set email alerts
|

A Is for Apple: the Role of Letter–Word Associations in the Development of Grapheme–Colour Synaesthesia

Abstract: This study investigates the origins of specific letter-colour associations experienced by people with grapheme-colour synaesthesia. We present novel evidence that frequently observed trends in synaesthesia (e.g. A is typically red) can be tied to orthographic associations between letters and words (e.g., "A is for apple"), which are typically formed during literacy acquisition. In our experiments, we first tested members of the general population to show that certain words are consistently associated with lett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 62 publications
4
41
2
Order By: Relevance
“…The findings of the current studies strengthen the view that grapheme-colour synaesthesia is a psycholinguistic phenomenon-the view that grapheme-colour synaesthesia builds on normal language processing [9][10][11][13][14][15]45]. Synaesthetic colours are elicited by grapheme attributes such as meaning (including semantic relations among abstract concepts) and sounds, and the development of lexicon and changes in lexical representation of graphemes may affect the synaesthetic colours.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The findings of the current studies strengthen the view that grapheme-colour synaesthesia is a psycholinguistic phenomenon-the view that grapheme-colour synaesthesia builds on normal language processing [9][10][11][13][14][15]45]. Synaesthetic colours are elicited by grapheme attributes such as meaning (including semantic relations among abstract concepts) and sounds, and the development of lexicon and changes in lexical representation of graphemes may affect the synaesthetic colours.…”
Section: Discussionsupporting
confidence: 79%
“…Asano & Yokosawa [10] showed that synaesthetic colours elicited by Kanji characters (characters of Japanese logographic script) representing a concrete meaning or an object with typical colours, such as 'red', 'blood' and 'cherry blossoms', are likely to be very consistent with the meaning. Similarly, Mankin & Simner demonstrated that synaesthetic colours for English alphabets can be predicted in part by early-learned letterword associations-for example, the synaesthetic colour for the letter 'A' tends to be red because A is for apple and apples are typically red ( [13]; but also see [31] which suggests that this effect may be language-specific). However, this type of semantic account can be applied only to graphemes that are tied to concrete meanings.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…When choosing the associations to be trained, we selected non-random letter-color pairings based on associations that are found for some synesthetes, as well as for nonsynesthetes when they are forced to select colors for letters (cf. Mankin & Simner, 2017; PERCEPTUAL PHENOMENOLOGY AND CORTICAL PLASTICITY 34 Simner et al, 2005). This design choice was made in order to maximize the likelihood of training success, in line with (and indeed replicating) our previous study (Bor et al, 2014; see also Supplemental Results).…”
Section: Control Studies and Limitationsmentioning
confidence: 99%
“…This question becomes even more relevant when considering that grapheme-colour associations are not unique to synaesthetes: non-synaesthetes, when forced to choose a colour for a grapheme, share some patterns of graphemecolour associations with synaesthetes [22][23][24]. However, studies comparing synaesthetes and non-synaesthetes show that while some patterns of grapheme-colour associations are shared, others are unique to synaesthetes or non-synaesthetes [22].…”
Section: Introductionmentioning
confidence: 99%